Diversity in teacher education : new expectations - Dilworth, Mary E.; American Association of Colleges for Teacher Education (San Francisco : Jossey-Bass, 1992)
The increasing racial and ethnic diversity of classrooms in the United States presents a significant challenge to the next generation of teachers and to those responsible for their training. This book explains the steps teacher educators and policymakers must take in order to prepare a teaching force that is both culturally diverse and culturally aware. Following a preface by the editor, the volume is organized into 12 chapters: (1) "Restructuring for a New America" (Carlton E. Brown); (2) "Preparing Teachers for Culturally Diverse Classrooms" (Antoine M. Garibaldi); (3) "Countering Parochialism in Teacher Candidates" (Nancy L. Zimpher, Elizabeth A. Ashburn); (4) "Understanding the Dynamics of Race, Class, and Gender" (Donna M. Gollnick); (5) "Making Teacher Education Culturally Responsive" (Jacqueline Jordan Irvine); (6) "Learning To Teach Hispanic Students" (Ana Maria Schuhmann); (7) "Recruiting and Retaining Asian/Pacific American Teachers" (Philip C. Chinn, Gay Yuen Wong); (8) "Accommodating the Minority Teacher Candidate: Non-Black Students in Predominantly Black Colleges" (Johnnie Ruth Mills, Cozetta W. Buckley); (9) "Tapping Nontraditional Sources of Minority Teaching Talent" (Richard I. Arends, Shelley Clemson, James Henkelman); (10) "Changing School Culture To Accommodate Student Diversity" ( Linda F. Winfield, JoAnn B. Manning); (11) "Diversifying Assessment: A Key Factor in the Reform Equation" (Leonard C. Beckum); and (12) "Restructuring for Diversity: Five Regional Portraits" (Sharon S. Nelson-Barber, Jean Mitchell).
Includes bibliographical references and indexes.
Keywords: Minorities -- Training -- United States; Minority teachers -- Education -- United States; Cultural pluralism -- Recruiting -- United States